Covid19, Sustainable Mobility and Transportation Research - Muhammad Ikhsan Setiawan; Ronny Durrotun Nasihien; Mohd Adib Mohammad Razi; Agus Sukoco,; Amrun Rosyid (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: Constructs and visualizes bibliometric networks research in Covid19, Sustainable Mobility And Transportation Research with meta-analysis techniques using VOS-viewer analysis. Design/methodology/approach: This research is a bibliometric analysis, a statistical evaluation of published books, or the chapters of a book, scientific articles in Covid19, Sustainable Mobility And Transportation Research, also it is an effectual way to measure the influence of publication in the scientific community. First analysis using Scopus.com analysis search result, Covid19, Sustainable Mobility And Transportation Research publication. Next analysis using VOS-viewer, a software tool for constructing and visualizing bibliometric networks in Covid19, Sustainable Mobility And Transportation Research field. Findings: Based on VOS-viewer analysis in scopus.com. COVID19, mobility and transportation research publication, 2020-2021, 134 document results, scopus.com, best 3 affiliations are Texas A&M University, The University of Sydney, and Griffith University; best 3 countries and territories are United Kingdom, United States, and Australia; best 3 funding sponsor are National Natural Science Foundation of China, European Commission, and European Research Council. Research limitations/implications: This research based on literature review. Practical implications: This research provides an illustration of sustainable mobility and transportation research in during the Covid-19 pandemic. Originality/value: This research is original. Paper type: Research Paper